A preliminary study of blastocystis hominis in some development areas in Alor Gajah District Melaka - Shafariatul Akmar Ishak,; Hidayatulfathi Othman,; Mazrura Sahani, (Penerbit UKM, 2008)
A descriptive study was conducted to evaluate the prevalence of Blastocystis hominis in children aged between 1-12 years old from randomly selected villages in Alor Gajah district Melaka. The sampling was carried out from 1 st to 7 th of July of 2006. A total of 48 faecal samples were obtained from the children in those studied villages. The faecal specimens were examined by direct saline wet moun, formalin ethyl acetate concentration and trichrome staining method. It was found that 45.8% (22 out of 48) of the examined children were infected with Blastocystis hominis . Based on the results, the cumulative prevalence of three methods used showed that Blastocystis hominis infection in female children higher compared to male children. Whilst the schooling children aged of 6 to 12 years had a higher prevalence than pre school children at the age of 1-5 years. In term of diagnosis, formalin ethyl acetate concentration method showed prevalence of detection at 60.9%. It was followed by direct saline wet mount (43.5%) and trichrome staining at 34.8%.